2022
DOI: 10.3390/jmse10111765
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Sulphur in Marine Residual Fuels by Deasphalting to Produce VLSFO

Abstract: This paper presents the results of the controlled sedimentation process for deasphalting, caused by targeted formation of the fuel dispersed system components incompatibility (proportion of the paraffins with normal structure increase) experimental investigations. The main purpose was to decrease the contained amount of sulphur in sedentary marine fuel and procure VLSFO. Developed and given account of the laboratorial method of instituting the sediment which modifies standard TSP and allows to control the deas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…2 consists of two components with different bases, paraffin-naphthenic in hydrotreated DF and predominantly aromatic with a high content of asphaltenes in visbreaking residue. Prior studies [66][67][68] have shown that such components show incompatibility, which is confirmed by the results of the experimental study of composition no. 2.…”
Section: Development and Study Of Properties Of The Model Composition...supporting
confidence: 67%
“…2 consists of two components with different bases, paraffin-naphthenic in hydrotreated DF and predominantly aromatic with a high content of asphaltenes in visbreaking residue. Prior studies [66][67][68] have shown that such components show incompatibility, which is confirmed by the results of the experimental study of composition no. 2.…”
Section: Development and Study Of Properties Of The Model Composition...supporting
confidence: 67%
“…During the study, for each of the cylinders, the maximum combustion pressure p z , the pressure at the end of compression p c , the average indicator pressure p i and the exhaust gas temperature t g were monitored. , … Δt g 8 -deviation of the exhaust gas temperature from the average value in the 1 st , 2 nd , … 8 th cylinders, respectively [39,40].…”
Section: Resultsmentioning
confidence: 99%
“…Fuel purification was provided in filters 2, 5, 8. The necessary concentration of FAME B30 biodiesel fuel in its mixture with DMA or RME180 fuel was provided by the dispenser 15 depending on the readings of the flow meter 13 and controlled by the microcontroller 14 [47,48].…”
Section: Methodsmentioning
confidence: 99%